Single proline substitutions of selected helices of the Bacillus thuringiensis Cry4B toxin affect inclusion solubility and larvicidal activity - I. Sramala (2018)
PCR-based mutagenesis was employed to investigate the role in toxicity of putative trans-membrane helices of the 130-kDa Cry4B mosquito-larvicidal delta-endotoxin produced by Bacillus thuringiensis subsp. israelensis. Mutant toxins with a single proline substitution in the central region of α5, α6 and α7 were constructed and expressed in Escherichia coli as cytoplasmic inclusion bodies with a yield similar to that of the wild-type toxin. Unlike inclusions of the wild-type and that of the previous mutants for proline replacements in α3 or α4, all proline-substituted inclusions were insoluble in carbonate buffer, pH 9.0, indicating that the bend introduced in these three helices possibly interferes with the protein inclusion packing as shown by the insolubility. Similar to the previous substitution in α4, an almost complete loss of toxicity against Aedes aegypti mosquito-larvae was demonstrated for E. coli cells expressing mutant toxins in which residues Val-181, Ala-182 or Leu-186 in α5 were changed to proline. In addition, a dramatic decrease in larvicidal activity was observed for the substitution at Thr-254 in α7 while the mutation Q215P in α6 did not affect the biological activity. These results suggest that the central helix (α5) and conceivably α7, but not α6, are important determinants of toxin function. Our data therefore further support the notion that the putative pore forming helical hairpin α4-α5 together with α7 plays a crucial role in Cry toxin activity.